Factors associated with poor outcome in tuberculous meningitis; study from a tertiary care referral Centre from South India - Neeharika L Mathukumalli; Sruthi Reddy Kola; Meena A Kanikannan; Suryaprabha Turaga; Rupam Borgohain (International Journal of Medical Research and Review, 2021)
Introduction: Tuberculosis (TB) remains a worldwide burden with a large majority of new active cases occurring in underdeveloped and developing countries. This study is an attempt to look into various aspects of the disease that can be associated with the outcome, to promote a timely referral to an appropriate centre. Purpose: To identify various clinical, lab, CSF and radiological variables associated with poor outcome of TBM at the time of discharge. Material & Methods: Demographic data, duration of symptoms before diagnosis, clinical presentation, staging of the disease at the time of admission of all the TBM patients who presented to our centre between December, 2015 and May 2018 were noted. Results of biochemical investigations and brain and spine imaging were retrieved. Outcome at the time of discharge as measured by MRC and mRS grades was correlated to clinical profile, lab, CSF and radiological findings. Results: A total of 100 patients were included. 15 patients died. Subjects with MRC and mRS grades of 2 or more at admission constituted 65% and 93% respectively. At discharge, MRC and mRS grades of 2 or more were found in 29.63% and 39% respectively. Multivariable analysis showed a significant positive association of MRC stage at discharge with MRC stage (p = 0.001) and mRS score (p = 0.001) at admission and Vellore hydrocephalus grade (p < 0.001) when hydrocephalus first identified. Similarly, mRS score at discharge had an independent positive association with the MRC stage (p < 0.001) and the mRS score (p=0.002) at admission. Conclusion: Stage of the disease (MRC) and functional status of the patient (mRS) at admission are the two most important independent factors determining the outcome of TBM patients at the time of discharge.